2014
DOI: 10.1089/ten.tec.2014.0067
|View full text |Cite
|
Sign up to set email alerts
|

A Multicompartment Holder for Spinner Flasks Improves Expansion and Osteogenic Differentiation of Mesenchymal Stem Cells in Three-Dimensional Scaffolds

Abstract: In the tissue engineering field dynamic culture systems, such as spinner flasks, are widely used due to their ability to improve mass transfer in suspension cell cultures. However, this culture system is often unsuitable to culture cells in three-dimensional (3D) scaffolds. To address this drawback, we designed a multicompartment holder for 3D cell culture, easily adaptable to spinner flasks. Here, the device was tested with human mesenchymal stem cells (MSCs) seeded in 3D porous chitosan scaffolds that were m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
4
3
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(14 citation statements)
references
References 43 publications
0
13
0
1
Order By: Relevance
“…Bone tissue engineering has been a primary focus of 3D scaffold development, and significant effort has been put into improving osteoblast adhesion and proliferation and ensuring that calcium deposition occurs in an appropriate manner. hMSCs that were cultured as spheroids using a porous 3D chitosan scaffold maintained in culture flasks with constant shaking for one week had an approximately sixfold increase of proliferated cells compared to static culture conditions with the same scaffold, and 3D PCL nanofiber scaffolds provide large surface areas for the cells and enhance MSC migration and proliferation.…”
Section: Stem Cell Biology In 3d Culturementioning
confidence: 99%
“…Bone tissue engineering has been a primary focus of 3D scaffold development, and significant effort has been put into improving osteoblast adhesion and proliferation and ensuring that calcium deposition occurs in an appropriate manner. hMSCs that were cultured as spheroids using a porous 3D chitosan scaffold maintained in culture flasks with constant shaking for one week had an approximately sixfold increase of proliferated cells compared to static culture conditions with the same scaffold, and 3D PCL nanofiber scaffolds provide large surface areas for the cells and enhance MSC migration and proliferation.…”
Section: Stem Cell Biology In 3d Culturementioning
confidence: 99%
“…Teixeira et al recently reported the beneficial effects of dynamic culture conditions (50 rpm) on the proliferation and osteogenic differentiation of commercially available hMSCs seeded onto chitosan disks (4 mm diameter and 3 mm thickness) for 14 days [58], as evidenced by improved cell distribution within the scaffolds, and increased matrix deposition and mineralization. Taken together, these results show that the dynamic conditions provided by spinner flask systems can support osteogenic differentiation and bone-like tissue formation, although these effects are also highly dependent on operation regimes and scaffold properties.…”
Section: Spinner Flasksmentioning
confidence: 99%
“…These approaches can be coarsely divided into two categories: (a) Dynamic approaches, using spinner flasks (Teixeira et al 2014) and rotating vessel bioreactors (Wang et al 2014); (b) Static approaches, based on non-adhesive surfaces (Hildebrandt et al 2011), gels (Cosson and Lutolf 2014) or hanging-drop plates (Bartosh et al 2010). Three major aspects must be considered when evaluating the advantages and disadvantages of each approach: efficiency, cost, and size of the produced spheroids (Mehta et al 2012;Alimperti et al 2014).…”
Section: Introductionmentioning
confidence: 99%